Systematic Literature Review on the Effect of Cooking Class on Picky Eaters in Early Childhood - Hasanah, Neneng; Mustapa, Noviana; Amini, Mukti; Choiriyah, Choiriyah; Riany, Yulina Eva (UIN Sultan Maulana Hasanudin Banten, 2025)
Picky eater behavior in early childhood can affect their growth and development, picky eater includes the behavior of choosing food only that they like and do not want to try new types of food, they then to avoid types of food in the form of vegetable protein and animal protein that are not yet known and felt. The impact of picky eater behavior is at risk of children experiencing malnutrition. Efforts to deal with picky eater behavior in children have been carried. Out with various interventions. This study uses a systematic literature review method, with the aim of finding out what interventions can be done to overcome picky eater behavior in children, as input for determining strategies in efforts to deal with picky eater behavior. This study obtained the results that picky eater behavior interventions can be carried out trough cooking class activities.